The fall of advertising and the rise of PR / Shifa Faizal - Faizal, Shifa (Faculty of Communication and Media Studies (FCMS), 2008)
According to the authors, great brands are built through the use of PR. This book focused on the greatness of building a brand using PR instead of advertising. Advertising has also been mentioned to live today only as a form of art, something that is invaluable, but has lost its true functions. As a believer of advertising, this book seemed rather intimidating.